Optimal Borrowing Policies for Developing Countries : The Cases of Korea, the Philippines, and Thailand. (IMF Working Papers; Working Paper ;, 1987)
This paper develops a theoretical framework for analyzing external debt policies of developing countries and applies it to assess the cases of three Asian countries, namely Korea, the Philippines, and Thailand. The 'optimal debt policy' for a developing country is characterized in the first part of the paper. In the second, the experiences of these three countries during the period 1965-83 are compared with this theoretical benchmark. The empirical results show that, during this period, Korea was quite successful in managing its external debt, while the Philippines was less successful. The case of Thailand, in many respects, fell in between the other two, although closer to that of Korea.